Does Full Exposure of Clusters Have Any Negative Effects on Tempranillo (Vitis vinifera L.) Grape Quality in La Rioja, Spain? The Use of Severe Cluster-zone Leaf Removal after Berry Set - Zheng, W.; García, J.; Balda, P.; Martínez de Toda, F. (South African Journal of Enology and Viticulture, 2017)
A three-year experiment comprising severe leaf removal (LR) was carried out on Tempranillo grapes in Logroño, North-central Spain. For the LR treatment, six basal leaves, along with the basal lateral shoots, were removed two weeks after fruit set. Berry total soluble solids (TSS) were examined when the colour began to appear. Grapes from both the LR and control (C) vines were analysed at the same TSS level (≈ 22°Brix). LR advanced the onset of anthocyanin synthesis slightly but significantly. Yield components were not affected by LR and no symptoms of sunburn were observed. Both treatments showed similar juice pH and titratable acidity, although tartaric acid increased with LR while malic acid decreased with it. In spite of failing to increase the final anthocyanin concentration of the grape juice, LR enhanced the colour and body of the wine. These results indicate that a relatively early LR could be a viable way to improve the quality of grapes and wine under the climatic conditions of the Rioja wine region.